2007
DOI: 10.1007/s00122-006-0495-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of MapPop1.0 for choosing a QTL mapping sample from an advanced backcross population

Abstract: QTL detection is a good way to assess the genetic basis of quantitative traits such as the plant response to its environment, but requires large mapping populations. Experimental constraints, however, may require a restriction of the population size, risking a decrease in the quality level of QTL mapping. The purpose of this paper was to test if an advanced backcross population sample chosen by MapPop 1.0 could limit the effect of size restriction and improve the QTL detection when compared to random samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…[16]. This was also observed by [10][11][12][13] who tested a SP strategy with the sampling method implemented in MapPop software. The benefits obtained with a selected sample, especially when specific genetic regions are targeted, were reported by Jin et al [14].…”
Section: Effect Of Sampling Strategy On the Detection And Mapping Of supporting
confidence: 61%
See 1 more Smart Citation
“…[16]. This was also observed by [10][11][12][13] who tested a SP strategy with the sampling method implemented in MapPop software. The benefits obtained with a selected sample, especially when specific genetic regions are targeted, were reported by Jin et al [14].…”
Section: Effect Of Sampling Strategy On the Detection And Mapping Of supporting
confidence: 61%
“…This selection should optimize the distribution of recombination points all over the genome. The effect of this selection procedure on QTL detection was evaluated in simulation [9] and empirical studies in different plants such as Arabidopsis [10], barley [11], maize [12] or pepper [13]. With the same objective, other authors proposed, through simulation studies, methods to select 1) individuals which maximize their genotypic dissimilarity using markers across the entire genome, markers on the chromosome that contained a known QTL or a single marker near the QTL [14]; 2) the individuals with a maximal number of recombination events considering (uniRec) or not (maxRec) the uniformity of their distribution across the genome [15].…”
Section: Introductionmentioning
confidence: 99%
“…the expected maximum distance between two points subjected to recombination. As previously reported by Birolleau-Touchard et al (2007), the best sample is the one with the most similar eMBL value compared to the original population obtained with a defined computational time and a chosen sample size. As a consequence, several iterations were run, until no further improvement in eMBL was achieved (data not shown).…”
Section: Choice Of Informative Individualsmentioning
confidence: 58%
“…This reduced subset is further submitted to phenotyping, reducing the field experiments while losing as little information as possible. Such strategies where evaluated by Vales et al (2005) and Birolleau-Touchard et al (2007). They showed that the MapPop sampling method permits to select population samples with balanced allele frequencies, and was superior to random sampling, particularly when QTL analysis has to be performed from unbalanced populations (doubled haploid or advanced backcross populations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation